300 Asthma-related sudden death in competitive athletes. (3rd March 2020) - Price, Oliver; Kucera, Kristen; Price, Hannah; Drezner, Jonathan; Menzies-Gow, Andrew; Hull, James
Abstract : Background: Asthma is highly prevalent in athletes, yet in the majority of cases can be managed and controlled effectively using standard inhaler therapy. Despite this, asthma as a cause of mortality in athletes has previously been reported. Objective: To provide a longitudinal evaluation of the incidence of asthma-related sudden death in competitive athletes. Design: Retrospective analysis of the United States (US) National Center for Catastrophic Sports Injury Research (NCCSIR) database between 1982–2018. Setting: Competitive US youth, high school, and collegiate sports. Patients (or Participants): Fatal asthma-related cases in competitive athletes were identified through media surveillance and reporting to the national center. Interventions (or assessment of risk factors): Information concerning sudden death was obtained via autopsy reports and/or news or media reports. Athlete age, sex, sporting discipline/event, year of death and cause of death were examined. Main outcome measurements: Total recorded deaths. Results: One thousand two hundred and ninety seven cases of sudden death were identified over the 36-year study period. Of these, 59% were attributed to a cardiac aetiology; 15.3% to catastrophic traumatic brain injury; 7% to heat stroke; 3.4% to other traumatic injury; 2.5% to commotio cordis; 2.1% to asthma; 1.7% to cervical spine injury; and 9% to all other causes. Of note, ten cases of sudden death attributed to a cardiac-aetiology (primary cause listed) also had a confirmed asthma diagnosis. Accordingly, thirty-seven asthma-related cases were identified over the study period. Asthma deaths occurred most frequently in young athletes (age range: 12–22 years) regularly participating in high-intensity intermittent-based sports: American football (59.5%); basketball (13.5%); soccer (10.8%); swimming (5.4%); wrestling (2.7%); volleyball (2.7%); cheerleading (2.7%); and other (2.7%). Conclusions: Asthma remains an important cause of sudden death in young athletes. Over the study period, approximately one athlete died per year, thus highlighting the importance of improved detection and care for athletes with asthma.